The growth, respiration, and reproduction of crustaceans: a synthesis through the Gill-Oxygen Limitation Theory (GOLT). Issue 4 (30th December 2022) - Pauly, Daniel; Amarasinghe, Upali S; Chu, Elaine; Freire, Kátia Meirelles Felizola; Vázquez, Elsa; Butler, Mark J
Abstract: Gill surface area (S) and respiration (R) in juvenile and adult crustaceans scale with their body weight (W) such that S ∝ R ∝ W d, with d ranging mostly between 0.6 and 0.9, but always <1, as in other water-breathing ectotherms (WBE). The growth of adult crustaceans therefore approaches an asymptote, whether or not seasonal growth oscillations are explicitly considered in the model used to describe that growth (e.g., von Bertalanffy growth function). On the other hand, the variation in asymptotic size (L∞ or W∞ ) among crustaceans is primarily determined by water temperature, which impacts on the oxygen requirements of WBE. Through multiple examples, this and related aspects of the Gill-Oxygen Limitation Theory (GOLT), first developed for fishes and later extended to other WBE, are shown to also apply to the growth of a wide range of crustacean taxa. The GOLT also explains certain aspects of crustacean reproduction, such as the relationship between size at first maturity and maximum size, and, possibly, the feature that female crustaceans hold their eggs outside of their bodies instead of internally.